2020
DOI: 10.1111/fog.12513
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the effects of environmental factors and fishing on abundance variability of Pacific saury (Cololabis saira) in the western North Pacific Ocean during 1982–2018

Abstract: Pacific saury (Cololabis saira) has a 2‐year life span and age‐1 fish migrates from the central and western North Pacific to Japanese waters from summer to winter. To understand interannual abundance variability of Pacific saury in the North Pacific, we examined the extended Japanese standardized catch per unit effort (esCPUE) with generalized linear models (GLMs) during 1982–2018. Explanatory variables included proxies of total and non‐traditional fishing effort (Ettl and Ent) and environmental factors. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recent studies demonstrated that rather than increased fishing effort, unfavourable conditions both in the spawning ground in Kuroshio waters and the nursery ground in Oyashio waters resulted in the large decline in the catch and biomass of Pacific saury (Liu et al, 2019; Xing et al, 2022). On the other hand, Yatsu et al (2020) hypothesized that abundance variability of Pacific saury during 1982–2018 was driven by environmental factors and fishing, with the latter exerting more adverse effect after 2016. The Japanese catch of Pacific herring depends primarily on the Hokkaido‐Sakhalin stock (Nagasawa, 2001) and this stock did not recover even in the cold period after the middle 1970s (Figure 1), but has recovered since 2015 (Ivshina, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that rather than increased fishing effort, unfavourable conditions both in the spawning ground in Kuroshio waters and the nursery ground in Oyashio waters resulted in the large decline in the catch and biomass of Pacific saury (Liu et al, 2019; Xing et al, 2022). On the other hand, Yatsu et al (2020) hypothesized that abundance variability of Pacific saury during 1982–2018 was driven by environmental factors and fishing, with the latter exerting more adverse effect after 2016. The Japanese catch of Pacific herring depends primarily on the Hokkaido‐Sakhalin stock (Nagasawa, 2001) and this stock did not recover even in the cold period after the middle 1970s (Figure 1), but has recovered since 2015 (Ivshina, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…high correlation with the decadal-scale stock fluctuations of dominant fish species, including the Pacific Decadal Oscillation (PDO) (Mantua et al, 1997;Chavez et al, 2003), North Pacific index in winter (NPI) (Trenberth and Hurrell, 1994;Yasunaka and Hanawa, 2002), North Pacific Gyre Oscillation index in winter (NPGO) (Di Lorenzo et al, 2008;Yatsu et al, 2021), and Arctic Oscillation index in winter (AO) (Thompson and Wallace, 1998;Ohshimo et al, 2009). Meanwhile, local oceanic environments, such as sea surface temperature (SST) in the Kuroshio Extension, have also been reported to influence the dynamics of stock fluctuations of commercial fish species (Noto and Yasuda, 1999).…”
mentioning
confidence: 99%